Association between maternal undernutrition and low birth weight: A hospital-based study in Chennai - Ramesh, Shanthi; Sundari, S; Harsha, M (Indian Journal of Child Health, 2019)
Background: Birth weight is an important predictor of a child’s growth and survival and this is dependent on the maternal health and nutrition during pregnancy. Objective: The objective of this study was to study the association between maternal nutritional status as measured by anthropometry, sociodemographic characteristics, and the birth weight of neonates. Materials and Methods: A hospital-based cross-sectional study was conducted among 100 singleton term newborns and their mothers between September 2017 and December 2018. Demographic and socioeconomic details such as maternal age, education, occupation, religion, and household income were recorded using a pre-structured questionnaire. The weight and height of all the mothers were measured. The babies were examined and the weight was recorded at birth. Results: The prevalence of low birth weight was found to be 21%. The mean birth weight was 2955±418 g. Maternal undernutrition (p=0.03), maternal short stature (p=0.04), maternal illiteracy (p=0.01), and lower socioeconomic status (p=0.05) were significantly associated with increased prevalence of low birth weight. Conclusion: The prevalence of low birth weight was found to be high. Maternal undernutrition was significantly associated with low birth weight. Hence, there is a need for continued focus on maternal nutrition for optimal intrauterine growth, thereby reducing the prevalence of low birth weight in India.